Determination of temporal value of a-value and b-value to identify the level brittle of rock and seismic activity in the Palu region - Afryanti Veronika Simangunsong; Ramadhan Priadi; Anak Agung Istri Dwilyantari; Agus Marsono (Universitas Sebelas Maret, 2019)
The Palu area is a region that has a high seismic potential as a result of the existence of the Palu Koro Fault. The Koro Palu Fault is an active sinistral fault that moves with velocity around 25-30 mm/year. This research purpose to determine the a-value and b-value temporally for identify rock brittle levels and seismicity levels in the Palu area using the Maximum Likelihood Guttenberg-Richter method. The data used in this study are earthquake data from the BMKG and USGS catalogs for 2008-2018 over a period of 10 years located at 0840 LU 40 2.620LS and 118,590 BT - 121.70 BT. Based on the results of data processing, there were 3033 earthquake distributions in the earthquake over a 10-year period. The calculation results show variations in the value of b-values in the range 0.55-0.961 and the a-value in the range 3.63-5.42. The highest b-value was obtained in 2015 at 0.961 as an indication of increased seismic activity in the Palu area. After the Palu M 7.4 earthquake on 28 September 2018, there was a significant decrease in the value of the b-value to 0.685. Based on the trend of b-value values which continued to decline from 2015 until 2018, it was identified in the rock's resistance to stress is high in the Palu area. Whereas for the seismicity index value of the Palu area of 0.040789 with the earthquake return period 7 is 25 years.